An easy method for reliable valuation of flash point temperature of organic ethers. (15th March 2023) - Nazari, Behzad; Keshavarz, Mohammad Hossein; Ramezani, Hossein
Graphical abstract: Abstract: Organic ethers are volatile and flammable because there are no significant intermolecular forces between their molecules and their uses require safety assessments in industrial processes. They have a wide variety of industrial uses such as primers for gasoline engines, fuel additives, commercial solvents, and rocket propellants but the measurements of the flash point of toxic and hazardous organic ethers are very difficult. This work introduces a simple method for a reliable prediction of the flash point of various types of organic ethers, which can be easily applied for estimation of the flash point of many organic ethers where their experimental values are not available in the literature. Different types of 121 organic ethers are used to derive and test the new correlation by considering the number of the number of carbon, oxygen, nitrogen, and chlorine atoms as well as the contribution of hydroxyl or specific group and lowering flash point fragments. The great consistency of the novel approach is compared with the results of one of the best existing methods where the values of Mean Absolute Percent Error (MAPE) of the new and two comparative models are 2.38, 4.67, and 6.10, respectively.